Standard feeding strategies with natural insemination improved fertility in repeat breeding dairy cows - Hasan, Mir; Hasan, Moinul; Rashid, Mohammad; Rahman, Marzia; Rahman, Md; Juyena, Nasrin (Journal of advanced veterinary and animal research, 2021)
Objective: The experiment was designed to establish suitable management strategies through the different feeding and breeding approaches on fertility improvement in the experimental repeat breeding (RB) cows. Materials and Methods: 80 RB cows were selected for this experiment. Before grouping, all cows were deworming and then divided into four equal groups, namely Group-TF1 [traditional feeding practice and natural insemination (NI)], Group-TF2 [traditional feeding practice and Artificial insemination (AI)], Group-SF1 [standard (STD) feeding practice and NI], and Group-SF2 (STD feeding practice and AI). These allocated RB cows were fed by traditional and STD feeding methods for 90 days and then inseminated by AI and NI breeding systems. The dominant follicle (DF) diameter, hemato-biochemical elements, and estrogen (E2) hormone were estimated during the insemination of cows. Estimation of the pregnancy rate was carried out at days 45-90 post-insemination in the cows. Results: The pregnancy rate was significantly (p < 0.05) higher in STD feeding practice with NI when compared to traditional feeding practice irrespective of breeding systems, and it was also significantly (p < 0.05) higher in NI than in AI breeding system, irrespective of feeding strategies. The results also showed that the diameter of DF, serum E2, total erythrocyte count, hemoglobin, packed cell volume, total cholesterol, total protein, glucose, calcium, phosphorus, ferric iron, copper, zinc, and magnesium at the time of insemination were significantly (p < 0.01) elevated in the experimental RB cows with STD feeding practice. The diameter of DF and serum E2 were significant (p < 0.01) and positively correlated with all hemato-biochemical elements in the cows at the time of insemination. Conclusion: The results suggest that NI with STD feeding practice may increase fertility in RB cows by improving general health status. Finally, it could support the veterinarians and researchers to define the management strategies using feeding and breeding strategies to prevent repeat breeding syndrome in dairy cows.